The influence of the Digital Divide on Big Data generation within supply chain management. Issue 2 (14th May 2018) - Gravili, Ginevra; Benvenuto, Marco; Avram, Alexandru; Viola, Carmine
Abstract : Purpose: The purpose of this paper is to examine the influence of the Digital Divide (DD) and digital alphabetization (DA) on the Big Data (BD) generation process, to gain insight into how BD could become a useful tool in the decision-making process of supply chain management (SCM). Similarly, the paper aims to recognize and understand, from a value-creation perspective, the correlation between DD and BD generation and between DD and SCM. Design/methodology/approach: The approach utilized in the present study consists of two steps: first, a systematic literature review was conducted aiming at finding out to determine the existing relationship between "Big Data Analytics" (BDA), "SCM" and the "DD". A total of 595 articles were considered, and analysis showed a clear relationship among BDA, SCM, and DD. Next, the Vector autoregressive (VAR) approach was applied in a case study to prove the correlation between DD (as part of internet usage) and internet acquisitions, and in general terms the relationship between DD and Trade. Internet usage and internet acquisition in imports and exports at the European level were considered as variables in an empirical study of European trade. The novelty of this two-tiered approach consists in its application of a systematic literature review, the first of its kind, to generate inputs for the longitudinal case study of imports and exports at the EU level. In turn, the case study tested the accuracy of the theorized relationship among the main variables. Findings: By analyzing the connection between DD and internet acquisitions, a positive and long-lasting impulse response function was revealed, followed by an ascending trend. This suggests that a self-multiplying effect is being generated, and it is reasonable to assume that the more individuals use the internet, the more electronic acquisitions occur. We can thus reasonably conclude that the improvement of the BD and SCM process is strongly dependent on the quality of the human factor. Tackling DA is the new reading key in the decision-making process: quantifying the added value of the human factor in SCM is challenging and is an ongoing process, based on the opportunity cost between automation in decision-making or relying on the complexity of human factors. Research limitations/implications: One of the biggest limits in our research is the lack of the time series available on consumer orientations and preferences. Data on the typology of customer preferences, and how they are shaped, modified, or altered, were non-accessible, though big companies may have access to this data. The present longitudinal study on European trade helps clarify how and to what extent BDA, SCM, and DD are inter-related. The modeling of the theoretical framework likewise highlights several identifiable benefits for companies of adopting BDA in their business processes. Practical implications: Understanding the obstacles to DD in trade companies and states, and identifying their influence on firm performance, serves to orient the decision-making process in SCM toward reducing DD to generate important economic benefits. Enhancing internet usage may accelerate longer-term investments in human resources, offering developing countries unprecedented opportunities to enhance their educational systems and to improve their economic policies, widening the range of opportunities for businesses and poor states. Social implications: BD generation will undeniably influence microeconomic decisions: they will become evaluation tools of more efficient economic progress in small and/or large economies. However, an economically efficient society will be achievable only in those countries in which qualified human resources can generate and manage BD, to unlock its potential. This twofold effect will surely affect the socio-economic and geopolitical situation. The economic progress of conventional countries may vacillate if it is not adequately flanked by qualified human resources able to progress the information and communication technology (ICT) prevalent in contemporary economies. Consequently, the social impact of investments in ICT capacity building will necessarily affect future socio-economic scenarios. New indicators will become necessary to measure the conventional progress, and one of them will surely be DD. Originality/value: The novelty of the present study is twofold: first, it is the first meticulous meta-analysis developed using a very wide analysis of the published literature to highlight a previously hidden relationship among DD, BD, and SCM. This comparative approach made it possible to build a theoretical framework for the real evaluation of the impact of BDA on different organizational elements, including SCM. Second, the research emphasizes the need to reform and reshape the studies on BDA, convincing companies that it is necessary to understand that the obstacles (DD and DA, i.e. internet usage) must be addressed with conscious decision-making processes, strategically and resolutely, to transform points of weakness into opportunities.